An Experimental Study to Determine the Antibacterial Activity of Selected Petroleum Jellies against Selected Bacteria that cause Skin Infections. - Tumwine , Joseph; Kitimbo , Joshua; Buyinza Seguya Yiga, Lameka; Kateregga , John; Turyamubona , Agnes; Mboowa , Gerald (Student's Journal of Health Research Africa, 2022)
Background: The skin is the largest organ of the body and forms its first line of defense against pathogens. When the integrity of this natural protective barrier is compromised, it’s an opportune moment for pathogenic microorganisms such as Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pyogenes among others to invade the body causing skin infections such as folliculitis, acne, impetigo among others. Objectives: This study aimed at determining the phytochemical profile of the selected petroleum jellies, determining the antibacterial activity of different petroleum jellies on selected bacteria causing skin infections, comparing the antibacterial activity of the jellies to that of the commonly used drugs against skin infections, and determining the minimum inhibitory concentration (MIC) of the jellies exhibiting antibacterial activity. Methods: The antibacterial activity of the jellies was determined by the agar well diffusion method (AWD) and the minimum inhibitory concentration (MIC) was determined by the broth dilution method. Results: Only herbal jellies exhibited antibacterial activity against at most two of the three bacterial species studied. The MIC values for the herbal jellies ranged from 47 mg/ml to 188 mg/ml. Conclusion: The non-herbal petroleum jellies did not show antibacterial activity while that of herbal jellies was minimal with very low potency and thus should not be relied on for wound healing or curing skin infections. Recommendations: The antibacterial activity of jellies should be tracked diligently to detect and address antimicrobial resistance as it arises to ensure that they remain efficacious.